Antioxidant Effect of Melatonin on the Functional Activity of Colostral Phagocytes in Diabetic Women - Morceli, Gliciane [UNESP]; Honorio-França, Adenilda C.; Fagundes, Danny L. G. [UNESP]; Calderon, Iracema de Mattos Paranhos [UNESP]; França, Eduardo L. (Public Library of Science (PLoS), 2013)
Melatonin is involved in a number of physiological and oxidative processes, including functional regulation in human milk. The present study investigated the mechanisms of action of melatonin and its effects on the functional activity of colostral phagocytes in diabetic women. Colostrum samples were collected from normoglycemic (N = 38) and diabetic (N = 38) women. We determined melatonin concentration, superoxide release, bactericidal activity and intracellular Ca2+ release by colostral phagocytes treated or not with 8-(Diethylamino) octyl-3,4,5-trimethoxybenzoate hydrochloride (TMB-8) and incubated with melatonin and its precursor (N-acetyl-serotonin-NAS), antagonist (luzindole) and agonist (chloromelatonin-CMLT). Melatonin concentration was higher in colostrum samples from hyperglycemic than normoglycemic mothers. Melatonin stimulated superoxide release by colostral phagocytes from normoglycemic but not hyperglycemic women. NAS increased superoxide, irrespective of glycemic status, whereas CMTL increased superoxide only in cells from the normoglycemic group. Phagocytic activity in colostrum increased significantly in the presence of melatonin, NAS and CMLT, irrespective of glycemic status. The bactericidal activity of colostral phagocytes against enterophatogenic Escherichia coli (EPEC) increased in the presence of melatonin or NAS in the normoglycemic group, but not in the hyperglycemic group. Luzindole blocked melatonin action on colostrum phagocytes. Phagocytes from the normoglycemic group treated with melatonin exhibited an increase in intracellular Ca2+ release. Phagocytes treated with TMB-8 (intracellular Ca2+ inhibitor) decreased superoxide, bactericidal activity and intracellular Ca2+ release in both groups. The results obtained suggest an interactive effect of glucose metabolism and melatonin on colostral phagocytes. In colostral phagocytes from normoglycemic mothers, melatonin likely increases the ability of colostrum to protect against EPEC and other infections. In diabetic mothers, because maternal hyperglycemia modifies the functional activity of colostrum phagocytes, melatonin effects are likely limited to anti-inflammatory processes, with low superoxide release and bactericidal activity. © 2013 Morceli et al.
Keywords: 3,4,5 trimethoxybenzoic acid 8 (diethylamino)octyl ester; chloromelatonin; luzindole; melatonin; n acetylserotonin; superoxide; unclassified drug; adult; bactericidal activity; calcium transport; cell function; clinical article; colostrum; controlled study; enteropathogenic Escherichia coli; female; glucose metabolism; human; human cell; maternal diabetes mellitus; nonhuman; phagocyte; phagocytosis; Adolescent; Adult; Antioxidants; Calcium; Colostrum; Cross-Sectional Studies; Escherichia coli; Female; Humans; Hyperglycemia; Melatonin; Middle Aged; Phagocytes; Phagocytosis; Pregnancy; Superoxides; Young Adult